Noncarbon Support Materials for Polymer Electrolyte Membrane Fuel Cell Electrocatalysts - Wang, Yan-Jie; Wilkinson, David P; Zhang, Jiujun (Chemical reviews, 2011)
The developments in the field of several important kinds of noncarbon supporting materials in recent years are reviewed. The challenges for developing noncarbon supporting materials are analyzed, and the possible future research directions, in particular the material preparation methods, are also proposed. To address the issue of carbon oxidation, effort has been placed on developing alternative noncarbon materials for catalyst supports. As compared to carbon-based supports, some noncarbon materials and their supported Pt-based catalysts have shown unique structures, suitable physical and chemical properties, and high catalytic activity toward fuel cell reactions such as the oxygen reduction reaction and small alcohol electrooxidation. To make noncarbon-supported Pt-based catalysts practically feasible in PEM fuel cells, material improvements in electronic conductivity, solubility, chemical/electrochemical and thermal stability, and surface area are required.